Characterising Clusterbean (Cyamopsis tetragonoloba (L.) Taub.) Germplasm for Yield Components and Quality Traits - Dwivedi, N K; Bhandari, D C; Bhatnagar, Neelam; Dabas, B S (Annals of Arid Zone, 2016)
Five hundred and twenty indigenous collections of clusterbean from Gujarat. Haryana, Madhya Pradesh. Rajasthan and Uttar Pradesh. were studied for various morpho-agronomical and quality traits. A wide range of variations was observed. for plant height, days to 50% !lowering and maturity. number of branches. clusters and pods per plant. length of cluster and pod. number of pods per cluster, number of seeds per pod, size. shape and color of seeds, seed yield per plant. 100-seed weight and gum and protein content. Breeders may make use of the collections with desirable superior traits. Accessions IC 116568 and IC 116906 had high seed yield per plant with high gum and protein contents.